Teach Me Your Arctic:Place-Based Intercultural Approaches in Art Education - Härkönen, Elina Maria (Journal of Cultural Research in Art Education, 2018)
In this article, I will discuss what a place-based approach in art education means for cultural understanding and culturally sustainable work in the context of the Nordic Arctic. I will approach and reflect these themes through art-based action research of the place-based art course “Our Arctic” that I organized with my colleagues at the University of Lapland in Spring 2017. The aim of the course in which art education and art students participated was to use artistic methods to collect and map the local school pupils’ perceptions of their lives in the Arctic and share these as a collective narrative in the form of a video art installation in an international exhibition. The approaches used in the course aimed to create knowledge that is locally and collaboratively produced and, in the process, also to see one’s own stance and cultural interpretations related to the Arctic.